Quality of Life among Chronic Renal Failure Patients Undergoing Hemodialysis at Teaching Hospital of Province 5 - Acharya, Sunita (Journal of Nursing Education of Nepal, 2023)
Introduction: Chronic renal failure is an irreversible progressive condition responsible for high  morbidity and mortality of the patients. It requires life-long treatment in the form of renal replacement  therapy, the quality of life (QOL) of patients may significantly impair. The objective of study was to  assess the quality of life of patients with chronic renal failure undergoing hemodialysis at Teaching  Hospital province 5, Banke Nepal.  Methods: Descriptive cross - sectional study design was used among 54 patients using non probability  purposive sampling technique. QOL was assessed using the World Health Organization Quality of life  (WHOQOL-BREF) questionnaire. Data were collected through interview technique and analyzed by  using descriptive and inferential statistics.  Results: Out of 54 patients 57.4% were male and 42.6% female. The mean age was 43.88± 12.56 SD.  Out of four domains (Physical, psychological, environmental and social), QOL scores were recorded:  over all QOL (64.53±13.22), physical domain (18.98±3.43), psychological domain (15.24±4.079),  environmental domain ((18.70±5.39) and social domain (7.66±1.94).The overall quality of life of  patients with chronic renal failure undergoing haemodialysis had poor quality of life among 57.40%  and high quality of life among 42.59%. There is moderate positive correlation (r=.569) between health  satisfaction and quality of life.
Keywords: Chronic kidney disease; Hemodialysis; Quality of life